Non Latin Latinitas: "Ius Latii" as a tool for the integration of provincial communities during the Republic - Sisani, Simone (Gerión. Revista de Historia Antigua, 2018)
This paper deals with some of the most problematic aspects of late Republican and early Imperial Latinitas: the diffusion in provincial contexts of the Latin colonization, the date of introduction of the ius adipiscendae civitatis per magistratum, the legal reasons underlying the creation in the last decades of the first century B.C. of the new category of the municipium Latinum.